A new clinical sign probably associated to left hemiplegia with left hemineglect syndrome: the crossed legs - Rodrigo Bazan; Thiago Fernandes; Gabriel Braga; Gustavo Luvizutto; Luiz Resende (Arquivos de Neuro-Psiquiatria)
Objective : To describe a new clinical sign associated with left unilateral neglect syndrome (UNS) in patients with ischemic stroke. Method : Head computed tomography (CT) and National Institute of Health Stroke Scale were obtained in 150 patients with ischemic stroke. Those with right cerebral vascular lesions, left hemiplegia and right leg persistently crossed over the left were submitted to specific tests for UNS. The tests were also applied to 30 patients with right cerebral vascular lesions, left hemiplegia but without crossed legs. Results : From 9 patients with persistent tendency to cross the right leg over the left, UNS was detected in 8. One patient died before the clinical tests were applied. Of the 30 patients without the crossed legs, 20 had normal clinical tests for UNS and 10 had minimal alterations, not sufficient for the diagnosis of UNS. Conclusion : The right leg crossed over the left may represent a new neurological semiotic sign associated with left hemiplegia and left UNS.